STATE OF THE ART IN HEXAPOD ROBOTS - Gheorghe GÎLCĂ (Fiabilitate şi Durabilitate)
This paper presents a study on hexapod robots, their main characteristics and the main types of walking. Moreover, the two most used types of walking are presented.